2016
DOI: 10.1007/s00394-016-1156-6
|View full text |Cite
|
Sign up to set email alerts
|

Difference in postprandial GLP-1 response despite similar glucose kinetics after consumption of wheat breads with different particle size in healthy men

Abstract: PurposeUnderlying mechanisms of the beneficial health effects of low glycemic index starchy foods are not fully elucidated yet. We varied the wheat particle size to obtain fiber-rich breads with a high and low glycemic response and investigated the differences in postprandial glucose kinetics and metabolic response after their consumption.MethodsTen healthy male volunteers participated in a randomized, crossover study, consuming 13C-enriched breads with different structures; a control bread (CB) made from whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Evaluation by the Cochrane RoB 2 tool identified 12 studies (48%) in the current review as having some concerns overall. Of these, 3 studies ( 38, 45, 52 ) had bias due to deviations from the intended intervention and 11 studies ( 32 , 34 , 38 , 39 , 47 , 48 , 50–53 , 56 ) had bias in measurements of outcomes. The other 13 studies were assessed as having low risks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation by the Cochrane RoB 2 tool identified 12 studies (48%) in the current review as having some concerns overall. Of these, 3 studies ( 38, 45, 52 ) had bias due to deviations from the intended intervention and 11 studies ( 32 , 34 , 38 , 39 , 47 , 48 , 50–53 , 56 ) had bias in measurements of outcomes. The other 13 studies were assessed as having low risks.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies ( 46 , 47 , 50–53 , 56 ) evaluated the effect of particle size on subjective satiety score iAUCs in healthy subjects. A meta-analysis was completed ( Figure 10 ) on the studies that supplied data ( 46 , 47 , 51–53 , 56 ) ( n = 98), and indicated that the particle size has no significant effect on subjective satiety scores (SMD = 0.02 mm*min; 95% CI: 0.19–0.24; P = 0.83).…”
Section: Resultsmentioning
confidence: 99%
“…A study [20] evaluating the five most common breads consumed in Spain, discovered that GIP release was higher after intake of wholemeal rather than white bread. Wheat bread consumption with different particle size elicited a GLP-1 response much lower after bread prepared with flour and 85% broken wheat kernels compared to a control bread made from wheat flour combined with wheat bran to obtain a similar fiber content [21].…”
Section: Relationship Between Incretin Hormones and Gimentioning
confidence: 99%
“…As noted above, vegetable-based diets are low acid producing diets, and high fiber consumption constitutes a dietetic strategy to control body weight and help prevent the onset of diabetes and insulin resistance [ 2 , 3 , 4 , 5 , 97 ]. Fiber intake stimulates satiety and it is correlated with decreased post-prandial insulin demand [ 98 ] by modulating glucose absorption and regulating gastrointestinal hormone-like peptides secretion [ 99 , 100 ] such as glucagon-like peptide 1 [ 101 ]. Hence, epidemiological studies reporting amelioration of insulin sensitivity following vegetable-based diet consumption should be interpreted in the context of effects elicited by fiber on energetic metabolism and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%